HUBUNGAN PENDIDIKAN TERHADAP TINGKAT KEPATUHAN MINUM OBAT DAN PENGARUHNNYA PADA KADAR GULA DARAH SEWAKTU PASIEN DIABETES MELITUS TIPE II DI RUANG RAWAT INAP RUMAH SAKIT X JAKARTA - Chusun, Chusun; Mira, Husni Sanjaya; Endang, Choiriah Lilis (Jurnal Riset Kefarmasian Indonesia, 2025)
Type 2 Diabetes Mellitus is a non-communicable chronic and progressive disease that can lead to increased blood glucose levels. Patient adherence to medication is essential for achieving therapeutic success. The objective of this study is to determine the relationship between education and medication adherence levels of Type 2 Diabetes Mellitus patients to blood glucose levels in the Emergency Department of the Polri Hospital, East Jakarta. This research method is non-experimental with an observational approach and a cross-sectional design using prospective data from medical records and direct interviews with patients in the inpatient room of Hospital X in Jakarta. The results of the study on 134 patients showed that the characteristics of Type 2 Diabetes Mellitus patients were: 34.3% (the majority) aged between 56 and 65 years, 60.4% female, 63.4% unemployed, 61.9% had elementary school education, and 60.4% had suffered from diabetes for more than 5 years. The most common comorbidity was CHF (Congestive Heart Failure), with 21 patients (15.6%). The level of medication adherence among patients was low, at 64.9%, and more than half (62.7%) had uncontrolled blood glucose levels. Meanwhile, the role of health education in reminding patients was categorized as good, at 91%. Based on the Bivariate Chi-Square analysis, there was a significant relationship between education and medication adherence, with a significance value of 0.000 (<0.005), and also between medication adherence and blood glucose levels (GDS) with a significance value of 0.000 (<0.005). It can be concluded that education affects medication adherence.